Reflections on extracting moral foundations from media content. Issue 3 (3rd July 2021) - Hopp, Frederic R.; Weber, René
ABSTRACT : Moral intuitions play a central role in communication processes, from the selection, valuation, and production of media content to political campaigning, opinion formation, and voting. The valid extraction of moral information from media content is a critical step toward understanding the dynamic transactions between moral frames and real-world events. In a recent case study, Wang and Liu (2021. Moral framing and information virality in social movements: A case study of #HongKongPoliceBrutality. Communication Monographs ) manually coded the presence of moral intuitions in tweets surrounding the hashtag #HongKongPoliceBrutality to examine how moral frames modulate a tweet's virality. Considering the numerous implications of this important work, we provide a commentary on Wang and Liu's approach and procedures. We hope that our commentary contributes additional insights into the challenges and state-of-the-art of moral content codings in communication studies.